External Trade Representations: Russian and Foreign Experience - Daniil A. Turlanov (Московский журнал международного права, 2016)
Export support of Russian non-raw products is one of the most crucial elements of the foreign trade regulation. Among such instruments of export support there is an institute of external trade representations of Russia. What is role of external trade representations in the frame of export support and what are perspectives of their development? The article gives the overview of external trade representations statues, the detailed analyze of the forms of export support, rendered by this trade instmment at external markets, description of export support foreign infrastructure, used by USA, France and Germany. On the basis of the best foreign practice the article proposes the ways of further development of Russian export support with the use of trade representations of Russia abroad.